2012
DOI: 10.4103/0019-5545.99532
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of factors associated with adolescent sexual activity

Abstract: Context:Adolescents constitute about 20% of our population and increasingly more of them are initiating sexual activity at an early age. Several behaviors associated with adolescence like masturbation, expression of masculinity/femininity, lifestyle habits like attending late night parties, and consumption of alcohol have been variously implicated in initiating sexual activities. Sexual abuse can also lead to premature sexualization. In view of few worthwhile studies from India that have dealt with these issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
(27 reference statements)
3
23
0
Order By: Relevance
“…Shashikumar et al, [13] has reported 6.31% boys and 1.31% girls having history of sexual activity in their study done on students of class IX to XII in two co-education schools of Pune. Bansal [14] had reported 25.2% of the adolescent truck cleaners had a history of sexual activity.…”
Section: Acknowledgementmentioning
confidence: 92%
“…Shashikumar et al, [13] has reported 6.31% boys and 1.31% girls having history of sexual activity in their study done on students of class IX to XII in two co-education schools of Pune. Bansal [14] had reported 25.2% of the adolescent truck cleaners had a history of sexual activity.…”
Section: Acknowledgementmentioning
confidence: 92%
“…Accordingly, although it is a public domain that sexual initiation among adolescents is happening increasingly early (5,8) , there is an enormous difficulty to accept as natural the sexual activity in this age group (18) . Trying to avoid or stop the sexual initiation of a teenager daughter, many families threat, reproach and criticize constantly.…”
Section: Discussionmentioning
confidence: 99%
“…Research regarding sexual experience in adolescents in India, Latin America and South Africa reveal elevated vulnerability in this age group (4)(5)(6) . The main indicated factors were early sexual initiation and need to adopt measures to help adolescents adopting safe sexual practices (5) ; insufficient information about sexual and reproductive health in advising services, having as consequence, a low number of adolescents sexually active being preventive against Sexually Transmitted Disease (STD) (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmarried pregnant girl and or having child is almost out of usual marriage market. However, studies show that pre-marital sex is not completely absent in India (Shashikumar et al, 2012;Ghule & Donta, 2011;Sujay, 2009;Alexander et al, 2007;IIPS & Macro International, 2007). Further, an extensive review of literature found that, in developing countries abortion and abortion related morbidity are most common among young unmarried women (Parker, 2005), which also implies that pre-marital sex among unmarried women in developing countries is not absent.…”
Section: Introductionmentioning
confidence: 99%